Recurrent respiratory papillomatosis: A challenging clinical entity - Santosh Kumar Swain; Sidharth Mohanty; Bulu Nahak; Mahesh Chandra Sahu (Apollo Medicine)
Recurrent respiratory papillomatosis (RRP) is a benign lesion seen in the respiratory airway caused by human papillomatosis virus (HPV).RRP can affects children to young adults. Most of the childhood RRP occur at birth which contaminated from birth canals of the mother. In adult ages, the infections transmitted via sexual route. The lesions are often seen as exophytic nodules, mostly in the larynx and occasionally at the nasopharynx, tracheobronchial trees and lung parenchyma. This disease is often unpredictable and varies from spontaneous remission to aggressive persistent or recurrence in nature.RRP has chance for malignant transformation to squamous cell carcinoma although it is a rare happening. The diagnosis is confirmed by histopathological study. Presently there is no definite treatment for RRP available. Surgery is the treatment of choice along with several adjuvant therapies available. The aim of this review article is to describe the detail etiology, epidemiology, clinical presentations, investigations and treatment of RRP.